Awareness Regarding Lithium Toxicity among the Caregivers of Mentally III Patients Attending a Tertiary Level Mental Hospital, Bagmati Province - Kayastha, Sujita Kumari; Sharma, Chandrakala; Bhattarai, Tilarupa (Journal of Nursing Education of Nepal, 2022)
Background: Lithium is the commonly used drug for bipolar affective disorders. Patient and family education about adverse effects, drug therapy and serum lithium monitoring are essentials to prevent and manage the lithium toxicity. Therefore, this study was conducted with the aim of finding out the awareness regarding lithium toxicity among the caregivers of patients receiving lithium. Method: A descriptive cross-sectional was adopted in this study. A total of 141 caregivers were selected purposively from the psychiatric outpatient department of Mental Hospital Lagankhel, Lalitpur over a period of four weeks from September 1st to 28th, 2019. Caregivers were interviewed using structured interview schedule. Data were analyzed by SPSS version 16. Descriptive and inferential statistics (chi-square test) were used to describe the socio-demographic variables and measure the association between level of awareness and selected socio-demographical variables. Results: The study findings revealed more than (52.5%) half of the family members were not aware of the fact that lithium may cause toxicity if taken inappropriately. There was no statistically significant association between the level of awareness and respondents’ socio-demographic variables. Conclusion: More than half of the caregivers are unaware of lithium toxicity. Thus indicates a need to provide information and education regarding lithium toxicity to the caregivers of patients taking lithium.